THE COMPARATION OF TWO LAPAN'S PROPELLANTS OF DIFFERENT COMPOSITION - Bagus H. Jihad; Tresna P. Soemardi; Dedi Priadi (National Institute of Aeronautics and Space - LAPAN, 2007)
This paper compares two LAPAN'S propellant compositions. The A propellant has a composition of AP/AL/Binder with ratio of 70/10/20, and propellant B has ratio 75/7.5/17.5, both with HTPB base but different curing agent. As comparator of this simulation is RX-1512.01 rocket that has flight tested. The performances which compared are specific impulse and efficiency characteristic. Result shows that the propellant B gives higher specific impulse, however higher losses is, about 5.373 percent. One to be considered is that the propellant B produce combustion temperature higher than propellant A by 200 k, that may influence the rocket structures. Keywords: Impuls specific, characteristic efficiency, propellant, simulation.